Pola Komunikasi dalam Penyelesaian Konflik Pasangan Nikah Muda di Desa Pangkah - Umdatul Khoirot; Mohammad Sa'diyin (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2020)
This young marriage is often associated with marriage at a young age or teenagers whose age has not reached 20 years (early marriage). But it is different again in relation to early marriage. Early marriage is more for underage children whose age is really below the limit for marriage, mostly like high school children and even junior high school students. Young marriage itself where marriage at a young age but it is already allowed to marry because of the age that has passed the limits of both legal and religious provisions. Young marriages usually have a lot of conflicts due to differences of opinion and others, one way to deal with conflicts is to apply good communication patterns. The pattern of communication is a picture of two or more people in the process of sending and receiving messages correctly, so that the intended message is conveyed or can be easily understood. The purpose of this research is to find out the reasons for getting married at a young age, to find out the communication patterns of young married couples in conflict resolution in Pangkah Wetan Village, Ujung Pangkah Gresik and to determine the factors that cause conflict between young married couples in Pangkah Wetan Village, Ujung Pangkah Gresik. In this study, researchers used descriptive qualitative research methods. The data collection procedure is interview, observation, and documentation. Checking the validity of the data carried out is triangulation. The results of this study indicate that: (1) the reasons for getting married at a young age in Pangkah Wetan Village Ujung Pangkah Gresik are parental/family factors, self-willed factors, and pregnancy out of wedlock. (2) communication patterns in resolving conflicts between young married couples in Pangkah Wetan Village, Ujung Pangkah Gresik, namely they are both silent until one of the partners or the guilty apologizes, but gradually their communication patterns are getting better and fulfill aspects of communication patterns in De Vito's theory. (3) the factors that cause conflict in young married couples are failure to communicate, economic factors, and difficulty accepting differences (natures).